Let Vb = the velocity of the boat.
Vw = the velocity of the flow of the stream.
X = the distance the boat traveled downstream.
So X = (Vb+Vw)T
After turning, the boat takes t time to get back to the float.
Then x -l = (Vb-Vw)t
and l = Vw * (T+t)
Replacing the equations for their variables you get (Vb+Vw)T-Vw(T+t) = (Vb-Vw)t
Simlify to: Vw = l/T+t = l/2T
Now using the values in the problem:
Vw = 12km / 2 * 60 = 12 km / 2hrs = 6km
The answer is 1. 6 km h^-1
(1) 2x + 3y = -11 (I am assuming you meant 2x + 3y instead of 2x + 3x at least?)
(2) x - y = 12
x = y + 12
If we substitute equation (2) into equation (1) we get:
2(y + 12) + 3y = -11
2y + 24 + 3y = -11
5y = -35, therefor y = -7
If y = -7, from equation (2) we get:
x = -7 + 12 = 5
Hope it can help you and mark me as a brainlist....